Environmental Changes and Societal Adaptations in Ancient Civilizations - Joseph, Maryam (European Journal of Historical Research, 2024)
Purpose: The aim of the study was to assess the environmental changes and societal adaptations in ancient civilizations. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Environmental changes have long been intertwined with societal adaptations in ancient civilizations. For instance, the Mesopotamians, who settled in the fertile lands between the Tigris and Euphrates rivers, built intricate irrigation systems to manage water scarcity. However, shifts in river courses or climatic variations challenged their agricultural practices, leading to innovations such as the use of canals and dams. In ancient Egypt, the annual flooding of the Nile was both a blessing and a curse. While it replenished the soil with nutrients, erratic floods could devastate crops and settlements. The Egyptians developed sophisticated levees and reservoirs to control the floodwaters, alongside religious rituals to appease the gods. Similarly, the Maya civilization in Mesoamerica grappled with environmental fluctuations, particularly in relation to rainfall patterns. They constructed elaborate water management systems, including reservoirs and cisterns, to mitigate the impact of droughts. Implications to Theory, Practice and Policy: Environmental determinism, social-ecological systems theory and cultural ecology may be used to anchor future studies on assessing the environmental changes and societal adaptations in ancient civilizations. Practitioners in fields such as archaeology, environmental science, and cultural heritage management should collaborate more closely to integrate diverse perspectives and methodologies in the study of environmental changes and societal adaptations in ancient civilizations. Policymakers should leverage insights from research on environmental changes and societal adaptations in ancient civilizations to inform contemporary environmental policy-making.